Development of wood wastes as fillers in the manufacture of thermoplastic composites - Kasim, Jamaludin; Shafie, Amran; Yamani, Shaikh Abdul Karim (2005)
Industrial wood wastes used in the study were collected from the various wood industry namely; sawmill, furniture and particleboard industry in Pahang. The wastes was firstly dried in an oven, and then screened to remove the oversize materials. The study was conducted to analyze the effects of filler loading (10, 30 & 50%), maleated anhydride polypropylene (MAPP) addition (0 & 3%) and the waste sources. The polypropylene was first melted in a dispersion mixer followed by the addition of MAPP a nd sawdust. The admixture was t hen compounded using a mould into test samples. The samples was tested for mechanical and water absorption properties according to British Standard Methods BS 2782. Filler was found to significantly affect all the thermoplastic composite properties. Higher filler loading showed that all the strength properties decrease while their modulus increases, and water absorption properties decreases significantly. MAPP only affected the tensile strength and modulus and its elongation at break. Waste sources affected all the properties except for water absorption. All waste sources (except for waste from karas wood) are potential fillers for the manufacture of polypropylene composites. The thermoplastic admixture can be use as the starting raw material in the production of products that do not require higher strength properties